A modified Bilirubin-induced neurologic dysfunction (BIND-M) algorithm is useful in evaluating severity of jaundice in a resource-limited setting - Radmacher, Paula G; Groves, Frank D; Owa, Joshua A; Ofovwe, Gabriel E; Amuabunos, Emmanuel A; Olusanya, Bolajoko O; Slusher, Tina M (BMC pediatrics, 2015)
Background Severe neonatal jaundice with associated acute bilirubin encephalopathy occurs frequently in low- and middle-income countries, where advanced diagnostic technology is in short supply. In an effort to facilitate the physical diagnosis of acute bilirubin encephalopathy, we pilot-tested a modified bilirubin induced neurologic dysfunction scoring algorithm in a group of pediatric trainees (residents) and their mentors (consultants) in a resource-constrained setting. Methods Jaundiced Nigerian infants were examined by consultant and resident pediatricians. The modified bilirubin induced neurologic dysfunction score assigned by residents was compared with the clinical diagnosis of acute bilirubin encephalopathy by expert consultants. Demographic information was obtained. Known risk factors were also evaluated among infants with and without acute bilirubin encephalopathy in addition to exploratory analyses. Data were analyzed by Statistical Analysis System; statistical significance was set at p < 0.05. Results Three hundred and thirty three paired modified bilirubin induced neurologic dysfunction scores (333) were analyzed and showed excellent agreement (weighted Kappa coefficient 0.7969) between residents and consultants. A modified bilirubin induced neurologic dysfunction score greater than or equal to 3 was highly predictive of a clinical diagnosis of acute bilirubin encephalopathy, with sensitivity of 90.7%, specificity of 97.7%, positive predictive value of 88.9%, and negative predictive value of 98.2%. Exposure to mentholated products was strongly associated with increased risk of acute bilirubin encephalopathy among those with known glucose-6-phosphate dehydrogenase deficiency (odds ratio = 73.94; 95% confidence interval = 5.425-infinity) as well as among those whose G6PD phenotype was unknown (odds ratio = 25.88; 95% confidence interval = 2.845-235.4). Conclusions The modified bilirubin induced neurologic dysfunction score for neonatal jaundice can be assigned reliably by both residents and experienced pediatricians in resource-limited settings as reflected in the algorithm’s sensitivity and specificity. It may be useful for predicting the development and severity of acute bilirubin encephalopathy in neonates.